Enzymatic Conversion of Geniposide to Genipin: A Natural Blue Color Precursor and Biopolymer Film Crosslinker - Thi Nga Vo; Dac Loc Ho; Hoang Duc Dang; Vinh Tien Nguyen (Journal of Technical Education Science, 2024)
The research is motivated by the growing interest in using natural products for biopolymer engineering, particularly in developing bioactive and biocompatible materials. Genipin, a natural blue colorant precursor, has garnered attention due to its unique chemical structure and crosslinking properties with natural polymers. This research focuses on the optimizing conditions for efficient enzymatic conversion of geniposide from Gardenia jasminoides into genipin and its subsequent utilization in producing chitosan-genipin films. Geniposide was extracted using 50% ethanol, and its enzymatic conversion to genipin using commercial cellulase was best at pH 4.5, 0.2 g cellulase per gram of geniposide and 6 h of reaction. The synthesized genipin was used to fabricate chitosan-genipin films, which were tested for various properties. The film with 0.01 w/w genipin/chitosan ratio exhibited the highest UV-vis absorbance at 610 nm, indicating significant crosslinking, and demonstrated the greatest mechanical strength at 19.92 N/mm². Additionally, this film showed a moisture content of only 2.01%, significantly lower than that of the control. Increasing the amount of genipin reacting with chitosan significantly reduced the moisture and swelling degree of the chitosan films, indicating their lower hydrophilicity. These results underscore the effectiveness of genipin as a crosslinking agent in biopolymer applications, suggesting its potential to develop sustainable materials with advanced mechanical and moisture-resistant properties.